Distinct Salmonella Enteritidis lineages associated with enterocolitis in high-income settings and invasive disease in low-income settings - Feasey, Nicholas A (2016)
Fil: Feasey, Nicholas A. Liverpool School of Tropical Medicine; Reino Unido.